Role of mitochondrial inner membrane organizing system in protein biogenesis of the mitochondrial outer membrane - Maria Bohnert; Lena-Sophie Wenz; Ralf M. Zerbes; Susanne E. Horvath; David A. Stroud; Karina von der Malsburg; Judith M. Müller; Silke Oeljeklaus; Inge Perschil; Bettina Warscheid; Agnieszka Chacińska; Marten Veenhuis; et al. (2012)
Mitochondria contain two membranes, the outer membrane and the inner membrane with folded cristae. The mitochondrial inner membrane organizing system (MINOS) is a large protein complex required for maintaining inner membrane architecture. MINOS interacts with both preprotein transport machineries of the outer membrane, the translocase of the outer membrane (TOM) and the sorting and assembly machinery (SAM). It is unknown, however, whether MINOS plays a role in the biogenesis of outer membrane proteins. We have dissected the interaction of MINOS with TOM and SAM and report that MINOS binds to both translocases independently. MINOS binds to the SAM complex via the conserved polypeptide transport-associated domain of Sam50. Mitochondria lacking mitofilin, the large core subunit of MINOS, are impaired in the biogenesis of β-barrel proteins of the outer membrane, whereas mutant mitochondria lacking any of the other five MINOS subunits import β-barrel proteins in a manner similar to wild-type mitochondria. We show that mitofilin is required at an early stage of β-barrel biogenesis that includes the initial translocation through the TOM complex. We conclude that MINOS interacts with TOM and SAM independently and that the core subunit mitofilin is involved in biogenesis of outer membrane β-barrel proteins.